Implementing intimate partner violence care in a rural sub-district of South Africa: a qualitative evaluation - Kate Rees; Virginia Zweigenthal; Kate Joyner (Taylor & Francis Group, 2014)
Background: Despite a high burden of disease, in South Africa, intimate partner violence (IPV) is known to be poorly recognised and managed. To address this gap, an innovative intersectoral model for the delivery of comprehensive IPV care was piloted in a rural sub-district. Objective: To evaluate the initiative from the perspectives of women using the service, service providers, and managers. Design: A qualitative evaluation was conducted. Service users were interviewed, focus groups were conducted amongst health care workers (HCW), and a focus group and interviews were conducted with the intersectoral implementation team to explore their experiences of the intervention. A thematic analysis approach was used, triangulating the various sources of data. Results: During the pilot, 75 women received the intervention. Study participants described their experience as overwhelmingly positive, with some experiencing improvements in their home lives. Significant access barriers included unaffordable indirect costs, fear of loss of confidentiality, and fear of children being removed from the home. For HCW, barriers to inquiry about IPV included its normalisation in this community, poor understanding of the complexities of living with violence and frustration in managing a difficult emotional problem. Health system constraints affected continuity of care, privacy, and integration of the intervention into routine functioning, and the process of intersectoral action was hindered by the formation of alliances. Contextual factors, for example, high levels of alcohol misuse and socio-economic disempowerment, highlighted the need for a multifaceted approach to addressing IPV. Conclusions: This evaluation draws attention to the need to take a systems approach and focus on contextual factors when implementing complex interventions. The results will be used to inform decisions about instituting appropriate IPV care in the rest of the province. In addition, there is a pressing need for clear policies and guidelines framing IPV as a health issue.